The other Adam Smith - Hill, Mike, 1964-; Montag, Warren (Stanford University Press, 2014)
The Other Adam Smith represents the next wave of critical thinking about the still under-examined work of this paradigmatic Enlightenment thinker. Not simply another book about Adam Smith, it allows and even necessitates his inclusion in the realm of theory in the broadest sense. Moving beyond his usual economic and moral philosophical texts, Mike Hill and Warren Montag take seriously Smith's entire corpus, his writing on knowledge, affect, sociability and government, and political economy, as constituting a comprehensive-though highly contestable-system of thought. We meet not just Smith the.